Sustainable strategic management in an emerging market economy: the case of Romanian women entrepreneurs. (21st December 2009) - Welsh, Dianne H.B.; Dragusin, Mariana
For decades the field of strategic management has been dominated by research on developed economies, especially those of USA and Europe. Emerging markets, such as the former Soviet bloc countries, have largely been ignored. These countries have experienced, in varying degrees, major political, economic and social changes that have had a major impact on their current entrepreneurial climate. Based on the new legal and institutional frameworks these former Soviet bloc emerging markets are establishing, the role women-owned businesses are playing to create economic growth and sustainable businesses are explored. The results showed similar findings in Romania compared to a similar study completed on women entrepreneurs in the Ukraine. Implications for sustainable strategic management in emerging economies are discussed.